1973
DOI: 10.1063/1.1680419
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the magnetic anomalies in Cu(II):Ni(II) bis(diselenocarbamate) crystals

Abstract: Articles you may be interested inInterpretation for the anomaly of the C=O stretching band in benzoic acid crystal J. Chem. Phys. 94, 4446 (1991); 10.1063/1.460634 14N nuclear quadrupole interaction in salicylaldoxime and in Cu(II) doped bis(salicylaldoxime) Ni(II) J. Chem. Phys. 74, 3618 (1981); 10.1063/1.441469Hartree-Fock-Slater-LCAO calculations on the Cu(II) bis(dithiocarbamate) complex; magnetic coupling parameters and optical spectrum A possible interpretation of the relevant magnetic anomalies, recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1974
1974
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The approach of Buluggiu and Vera (1973) parallels that of Hitchman et al (196913) and the more recent discussion of Belford et al (1977) and reviewed in $4.1.1. Buluggiu and Vera (1973) explained, in principle, the rotation of g relative to A in the plane normal to the two-fold axis. More recently Keijzers and de Boer (1975a, b) have presented rather more complete calculations using the extended Huckel method to both the monomeric and dimeric structures.…”
Section: Results Of Molecular Orbital Calculationsmentioning
confidence: 79%
See 2 more Smart Citations
“…The approach of Buluggiu and Vera (1973) parallels that of Hitchman et al (196913) and the more recent discussion of Belford et al (1977) and reviewed in $4.1.1. Buluggiu and Vera (1973) explained, in principle, the rotation of g relative to A in the plane normal to the two-fold axis. More recently Keijzers and de Boer (1975a, b) have presented rather more complete calculations using the extended Huckel method to both the monomeric and dimeric structures.…”
Section: Results Of Molecular Orbital Calculationsmentioning
confidence: 79%
“…Keijzers and de Boer (1972) reported use of the iterative extended Huckel molecular orbital method, which had been outlined previously (Keijzers et a1 1972), in calculations of A for copper (N,N-diethyldiselenocarbamate). Buluggiu and Vera (1973) presented a possible interpretation of the copper di-n-butyl diselenocarbamate results due to van Rens et a1 (1970) using an LCAO model based on metal d and ligand p orbitals. The approach of Buluggiu and Vera (1973) parallels that of Hitchman et al (196913) and the more recent discussion of Belford et al (1977) and reviewed in $4.1.1.…”
Section: Results Of Molecular Orbital Calculationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Following the observation of non coincidences between principal 9 and A directions for copper II n-butyl diselenocarbamate crystals by Van Rens et al (1970) and Kirmse et al (1972), Buluggiu and Vera (1973) and Keijzers and de Boer and co-workers (i.e., Attansio et aI., 1976) have shown that it is possible to obtain good agreement with experiment for quite complicated low-symmetry complexes. While many of the copper II sites in proteins may be low-symmetry ones, viz., C2 , C2h , C., Ci , or C b the resolution of the observed spectra do not allow conclusions to be drawn along these lines at the present time.…”
Section: Ligand Field Theorymentioning
confidence: 92%
“…spin Hamiltonian parameters (g-and A-) with changes in the nature of the ligand (substituent changes) in square planar copper(I1) con~plexes (CuL,) has been well studied and can be said to be fairly well understood (1)(2)(3)(4)(5)(6)(7). The dependence of the g-tensor and hyperfine coupling tensor (A) on the rigid matrix in which the square planar conlplex is situated has also been the subject of extensive study.…”
Section: Introductionmentioning
confidence: 99%